UV stabilization route for melt-processible PAN-based carbon fibers - Paiva, M. C. (2003)
Ultraviolet radiation-based stabilization routes were explored to produce carbon fibers from melt-processible PAN-based copolymers. An acrylonitrile /methyl acrylate (AN/MA) copolymer was melt-spun into fibers that were crosslinked using UV radiation. The fibers could then be stabilized by oxidative heat treatment, and subsequently carbonized. Physical and mechanical testing was performed to determine the degree of stabilization and the properties of the stabilized and carbonized fibers.